Migration and homeostasis of regulatory T cells in rheumatoid arthritis - Kotschenreuther, Konstantin; Yan, Shuaifeng; Kofler, David M. (Frontiers in Immunology, 2022)
Regulatory T (Treg) cells are garnering increased attention in research related to autoimmune diseases, including rheumatoid arthritis (RA). They play an essential role in maintenance of immune homeostasis by restricting effector T cell activity. Reduced functions and frequencies of Treg cells contribute to the pathogenesis of RA, a common autoimmune disease which leads to systemic inflammation and erosive joint destruction. Treg cells from patients with RA are characterized by impaired functions and by an altered phenotype. They show increased plasticity towards Th17 cells and a reduced suppressive capacity. Besides the suppressive function of Treg cells, their effectiveness is determined by their ability to migrate into inflamed tissues. In the past years, new mechanisms involved in Treg cell migration have been identified. One example for such a mechanism is the phosphorylation of vasodilator-stimulated phosphoprotein (VASP). Efficient migration of Treg cells requires the presence of VASP. IL-6, a cytokine which is abundantly present in the peripheral blood and in the synovial tissue of RA patients, induces posttranslational modifications of VASP. Recently, it has been shown in mice with collagen-induced arthritis (CIA) that this IL-6 mediated posttranslational modification leads to reduced Treg cell trafficking. Another protein which facilitates Treg cell migration is G-protein-signaling modulator 2 (GPSM2). It modulates G-protein couple receptor functioning, thereby altering the cellular activity initiated by cell-surface receptors in response to extracellular signals. The almost complete lack of GPSM2 in Treg cells from RA patients contributes to their reduced ability to migrate towards inflammatory sites. In this review article, we highlight the newly identified mechanisms of Treg cell migration and review the current knowledge about impaired Treg cell homeostasis in RA.